The Potential of Muhammadiyah as a Driving Force for Community Empowerment in Wonokoyo Village - Nurul Octavia; Muhlasin Amrullah; Fachriza Alma F.; Alifvia Putri L.; Vina Virgianata N.; Rahmadyanti Y. (Proceedings of The ICECRS, 2020)
Muhammadiyah movement is known as the movement of enlightenment. The enlightenment movement has a role to return the people to the right guidelines of life namely the Al Qur'an and the Sunnah. Muhammadiyah is also known as a large movement and spread throughout Indonesia, therefore to facilitate the delivery of religious knowledge to the community some branches or branches take care and observe the condition of this movement in each region. The purpose of this research is to recognize and understand how the development of the enlightenment movement in the environment around us in carrying out their duties and their contribution to society through programs that have been made to return people to the right direction and still hold fast to the Qur'an and sunnah or how Muhammadiyah's role in empowering the surrounding community. The method used is descriptive qualitative through observation and interviews with figures in the membership structure of Muhammadiyah who are in branches. The results showed that several excellent programs have been carried out by Muhammadiyah branches that deal directly with the Muhammadiyah community in the area itself, and through this program, many positive things have been created to enlighten the people.